Kształtowanie wyobraźni historycznej na przykładzie ćwiczenia adresowanego do studentów pierwszego roku historii UMK - Agnieszka Laddach, Agnieszka Laddach (Kultura-Społeczeństwo-Edukacja, 2020)
Laddach Agnieszka, The development of historical imagination on the example of an exercise addressed to firstyear students of history at Nicolaus Copernicus University. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 163–181, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.11. December 12, 2016 a group of eleven first-year students of history organized at the Institute of History of Nicolaus Copernicus University in Toruń (Poland) participated in the field work carried out in the church Roman Catholic parish of St. Jacob the Apostle in Toruń. During a visit in the temple the students performed an exercised to draw their attention: generally to the role of the imagination in the practice of the historian’s research and training his own imagination in whole live. First, the authoress described a process of the exercise. Then she briefly pointed to the literature on the role of the imagination. Later she discussed the work that have arisen in the result of the exercise. Next she characterized the thoughts and impressions of students. She also outlined the importance of this exercise in a broader context. At the end she summed up the whole article.